A critical analysis of the implementation of service user involvement in primary care research and health service development using normalization process theory. (24th July 2014) - Tierney, Edel; McEvoy, Rachel; O'Reilly‐de Brún, Mary; de Brún, Tomas; Okonkwo, Ekaterina; Rooney, Michelle; Dowrick, Chris; Rogers, Anne; MacFarlane, Anne
Abstract: Background: There have been recent important advances in conceptualizing and operationalizing involvement in health research and health‐care service development. However, problems persist in the field that impact on the scope for meaningful involvement to become a routine – normalized – way of working in primary care. In this review, we focus on current practice to critically interrogate factors known to be relevant for normalization – definition, enrolment, enactment and appraisal. Method: Ours was a multidisciplinary, interagency team, with community representation. We searched EBSCO host for papers from 2007 to 2011 and engaged in an iterative, reflexive approach to sampling, appraising and analysing the literature following the principles of a critical interpretive synthesis approach and using Normalization Process Theory. Findings: Twenty‐six papers were chosen from 289 papers, as a purposeful sample of work that is reported as service user involvement in the field. Few papers provided a clear working definition of service user involvement. The dominant identified rationale for enrolling service users in primary care projects was linked with policy imperatives for co‐governance and emancipatory ideals. The majority of methodologies employed were standard health services research methods that do not qualify as research with service users. This indicates a lack of congruence between the stated aims and methods. Most studies only reported positive outcomes, raising questions about the balance or completeness of the published appraisals. Conclusion: To improve normalization of meaningful involvement in primary care, it is necessary to encourage explicit reporting of definitions, methodological innovation to enhance co‐governance and dissemination of research processes and findings.